2016
DOI: 10.1016/j.vhri.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Related Metabolic Disorders, Osteoporosis, and Fracture Risk in Asia: A Systematic Review

Abstract: These findings suggest that diabetes is a risk factor for fracture in Asian populations. MetS may be associated with bone loss in Asian men and atherosclerosis associated with increased fractures; however, caution is needed interpreting these findings given limitations in study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 55 publications
3
32
0
1
Order By: Relevance
“…Although a proportion of patients in both the T2DM and non-DM groups developed clinical fractures during the follow-up period, the proportion in the T2DM group was significantly larger than in the non-DM group (12.7% vs 9.9%; P  < 0.001; Table 2). This difference reflects the additional fracture risk posed by T2DM (independent of osteoporosis), as has been observed in previous studies [4, 5, 8]. These findings suggest that both physicians and patients need to carefully consider the potential impact of T2DM on the treatment and management of osteoporosis in order to achieve the best clinical outcome and to ensure the most efficient use of healthcare resources.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although a proportion of patients in both the T2DM and non-DM groups developed clinical fractures during the follow-up period, the proportion in the T2DM group was significantly larger than in the non-DM group (12.7% vs 9.9%; P  < 0.001; Table 2). This difference reflects the additional fracture risk posed by T2DM (independent of osteoporosis), as has been observed in previous studies [4, 5, 8]. These findings suggest that both physicians and patients need to carefully consider the potential impact of T2DM on the treatment and management of osteoporosis in order to achieve the best clinical outcome and to ensure the most efficient use of healthcare resources.…”
Section: Discussionsupporting
confidence: 77%
“…Effective management of osteoporotic fractures requires careful evaluation not only of osteoporosis but also of the increasing number of comorbidities that are thought to influence the risk of fractures [4]. Diabetes is emerging as one of the most important comorbidities in terms of its impact on fractures, as suggested by studies in the USA and in Europe [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that there is an association between comorbidities and the risk of fracture with the most prevalent comorbidities as diabetes and cardiovascular diseases [15,16]. In our study, hypertension, coronary artery disease, and diabetes were found to be commonly occurring comorbidities.…”
Section: Discussionsupporting
confidence: 51%
“…Osteoporosis is a skeletal disorder characterized by low bone mineral density (BMD) and a compromised bone microarchitecture, which lead to increased risks of bone fragility and fracture [1]. Osteoporosis has become a major healthcare problem worldwide, affecting more than 200 million people [2]. There are gender differences in the occurrence of osteoporosis; postmenopausal women are more likely to have osteoporosis due to the sharp decline of estrogen production [3].…”
Section: Introductionmentioning
confidence: 99%